Antimicrobial Properties of Selected Plant Species within the Asteraceae Family - Angelo Randriatsalama; Njakarinala Ranarivelo; Vahinalahaja Razafintsalama; Rianatiana Ranaivoarisoa (Biology and Life Sciences Forum)
The Asteraceae family is the largest family of flowering plants, comprising over 25,000 species grouped into 16,000 genera and distributed around the world. This research aimed to evaluate the antibacterial effectiveness of 12 native plants from the Asteraceae family. Their efficacy was tested against 11 bacterial strains using the liquid microdilution technique to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). MIC values ranged from 0.125 to 4 mg/mL, and MBC values ranged from 0.25 to 4 mg/mL, against six bacterial strains. These results describe the potential antibacterial activity attributes of Asteraceae species.